Early Prenatal Diagnosis of Cornelia de Lange's Syndrome with Whole-Exome Sequencing: A Case Report - Iftikhar, Amna; Barnes, Kathleen; Figueroa, Melissa; Francis, Antonia P. (American Journal of Perinatology Reports, 2024)
Cornelia de Lange's syndrome (CDLS) is a multisystem genetic syndrome characterized by well-defined physical, intellectual, and behavioral characteristics. The diagnosis of CDLS is typically done clinically after birth; however, recent studies have demonstrated the ability to use prenatal ultrasound and whole-exome sequencing to diagnose CDLS prenatally. Here we present a prenatal case in which multiple fetal anomalies were identified on ultrasound at 20 weeks of gestation. Use of whole-exome sequencing allowed for successful diagnosis of CDLS in this fetus prenatally.
Keywords: Cornelia de Lange's syndrome; prenatal diagnosis; whole-exome sequencing; prenatal ultrasound; cohesinopathies